Aplikasi Pelayanan Masyarakat di Kelurahan Karanganyar Berbasis Web - Dimarzio Nugraha P; M Dimas Rifa P; Dicky Gustianto; Triana Nur R; Nurdianto Nurdianto (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
The public service process in Karanganyar sub distric has used the SIPAKU (Sistem Informasi Pelayanan Administrasi Kewilayahan Terpadu) application from the Bandung City office which is website-based. However, there are still many types of services that are not covered by SIPAKU, especially in submitting several types of letters. So the development of a new public service website was proposed to facilitate these services and complement the existing SIPAKU called APERKAR (Aplikasi Pelayanan Masyarakat Kelurahan Karanganyar). The website that was developed aims to make it easier for the public to submit various types of letters that were previously not covered by SIPAKU, such as SKTM, SKU, Marriage Introduction Letter, SKSG, and Institutional Domicile Letter without the public having to come directly to the Karanganyar sub distric office. The method used was to develop the website that was created and socialize it to the sub distric staff to later be socialized again to the public. The results of the website development that was created showed that the website can increase efficiency in administrative services, both in terms of ease of submitting letters for the public and data management by administrative officers.